Comprehensive handbook of psychological assessment Volume 1, Intellectual and neuropsychological assessment - Goldstein, Gerald, 1931-; Beers, Sue R.; Hersen, Michel (Hoboken, N.J. : John Wiley & Sons, 2004)
In one volume, the leading researchers in intelligence and neuropsychological assessment interpret the range of issues related to intellectual and neuropsychological tests, including test development and psychometrics, clinical applications, ethical and legal concerns, use with diverse populations, computerization, and the latest research. Clinicians and researchers who use these instruments will find this volume invaluable, as it contains the most comprehensive and up-to-date information available on this important aspect of practice.
Includes bibliographical references and indexes.
Print version record.
Keywords: Psychological tests; Neuropsychological tests; Intelligence tests; Electronic books